Obesity and the Cardiorenal Metabolic Syndrome: Therapeutic Modalities and Their Efficacy in Improving Cardiovascular and Renal Risk Factors - Jindal, Ankur (S. Karger AG, 2012)
The prevalence of obesity has increased rapidly in the United States. Obesity affects about one third of the adult population and, even though it is attributed to excess calorie intake and inadequate physical activity, its etiopathogenesis is much more complex and is an area of active study. Lifestyle modifications (with a focus on increased activity and decreased calorie intake) have modest efficacy in the treatment of obesity. There is a dearth of safe and effective therapeutic modalities to treat obesity. In this review, we discuss the role of different treatment options in the management of obesity and its comorbidities, with a focus on recently approved drugs and the emerging role of bariatric surgery.